Different distributions of T cell subsets between perivascular and interstitial peritubular areas during rejection of rat renal allografts: a quantitative and ultrastructural study using monoclonal antibodies. - Ishikura, H (1985)
Distributions and ultrastructures of T cell subsets within grafts were studied in unmodified, first-set rat renal transplantation systems (F344----WKA, TO----WKA). Rejections took place within 9.0 +/- 0.5 and 12.2 +/- 1.6 days, respectively. Mouse monoclonal antibodies, R1-3B3 and R1-10B5, were used here for the detection of RLyt-1 and RLyt-2 antigenic systems of rat T cells, respectively. RLyt-1 and RLyt-2 antigens are chemical homologues of mouse Lyt-1 and Lyt-2,3 antigens. In the perivascular areas, RLyt-1+,2- cells were the predominant T cells in earlier stages of rejection. However, toward the end of rejection, RLyt-1+,2- cells decreased in number, with the increase in RLyt-1+,2+ cells. In the interstitial peritubular areas, RLyt-1+,2+ cells were the predominant T cells throughout the course of rejection. Thus, the major T cells in perivascular areas were helper T cells in earlier stages and cytotoxic/suppressor T cells in the later stage, whereas in interstitial peritubular areas, cytotoxic/suppressor T cells were the major T cell population during the entire course of rejection. Ultrastructural studies revealed that many RLyt-2+ blast cells had clustered dense bodies, and that RLyt-2+ cells were found among renal tubular epithelial cells. Renal tubular cells adjacent to RLyt-2+ cells were degenerative in most cases. In addition, membranous structures seen in grafts were RLyt-1+,2+,Ia-, suggesting that they might derive from the destruction of cytotoxic/suppressor T cells after several target cell lyses in vivo.